Pattern, Severity and Outcome of Injuries Sustained in Road Traffic Accidents: A Tertiary Care Hospital-Based Study (Medicine Today, 2023)
Introduction:Road Expansion and motorization, in the country has been accompanied by a rise in road accidents leading to road traffic injuries (RTIs). Today RTIs are one of the leading causes of deaths, disabilities, and hospitalizations with severe socioeconomic costs across the world. The aim of the study is to determine the pattern, severity and outcome of injuries amongst road traffic accident victims.Materials & Methods: An observational study was carried out at casualty department of Cumilla Medical College Hospital, from April 2020 to September 2020. Total 192 patients following RTIs were included in this study. After history taking, clinical examination and collection of investigation reports, data was analyzed by using SPSS-23.Results: Out of 192 patients, 33.3% of the patients belonged to age group 21-30 years, 71.4% were male. More than two third (67.2%) patients accident took place in high way and 62 (32.8%) in other areas. According to pattern of victims 111(57.8%) patients was found in pedestrian of victims, 48(25.0%) in driver and 33(17.2%) in passenger. In injury severity score, 98(51.0%) patients were found minor injuries followed by 57(29.7%) moderate, 22(11.5%) serious and 15(7.8%) severe injuries. Ninety (46.9%) patients were found transfer for definitive care followed by 52(27.1%) discharge after Rx, 30(15.6%) wound infection, 18(9.4%) referred to higher center and 2(1.0%) death.Conclusion: The present study shows that fatal accidents mainly affected the young adults in productive age groups and pedestrians. Highways were most commonly affected location. Most of the accidents caused by motorized vehicles.Medicine Today 2023 Vol.35(2): 109-113